Essay: Making the most of recent advances in freshwater mussel propagation and restoration. Issue 7 (20th May 2019) - Strayer, David L.; Geist, Juergen; Haag, Wendell R.; Jackson, John K.; Newbold, J. Denis
Abstract: Propagating and releasing freshwater mussels (Unionida) into the wild can contribute substantially to conservation and perhaps ecosystem restoration, but poorly conceived projects can waste money and public good will, and harm mussel populations and ecosystems. Moving from vague, emotional reactions about mussel restoration to more rigorous discussions and analyses can help focus efforts to where they do the most good. We suggest that: (i) projects to restore mussels for conservation goals to sites where known environmental problems have been eliminated or mitigated have good prospects for success; (ii) projects to restore mussels for conservation goals to sites where known environmental problems have not been eliminated or mitigated have poor prospects for success; (iii) projects to restore mussels for conservation goals to sites in the common situation in which the status of environmental problems is unknown have unknown prospects for success, but may be valuable as scientific experiments, if project performance is monitored properly; (iv) the value of population augmentation as a conservation tool is uncertain, and needs better theoretical and empirical analysis; (v) assisted migration of mussels as a conservation tool is controversial, and should be discussed thoroughly before we reach crises in which it is rejected or carried out carelessly; (vi) projects to restore ecosystem services face more stringent criteria for success than conservation projects, and some such projects being discussed seem unlikely to succeed. Monitoring data on how restoration projects perform typically are inadequately collected, reported, disseminated, and used to improve practice. This could be improved by setting up a clearinghouse to collect, hold, and disseminate data; providing training to restorationists; and opening conversations between restorationists and data managers and statisticians.